Vascular access in children requiring maintenance haemodialysis: a consensus document by the European Society for Paediatric Nephrology Dialysis Working Group. Issue 10 (11th March 2019) - Shroff, Rukshana; Calder, Francis; Bakkaloğlu, Sevcan; Nagler, Evi V; Stuart, Sam; Stronach, Lynsey; Schmitt, Claus P; Heckert, Karl H; Bourquelot, Pierre; Wagner, Ann-Marie; Paglialonga, Fabio; Mitra, Sandip; et al.
Abstract: Background: There are three principle forms of vascular access available for the treatment of children with end stage kidney disease (ESKD) by haemodialysis: tunnelled catheters placed in a central vein (central venous lines, CVLs), arteriovenous fistulas (AVF), and arteriovenous grafts (AVG) using prosthetic or biological material. Compared with the adult literature, there are few studies in children to provide evidence based guidelines for optimal vascular access type or its management and outcomes in children with ESKD. Methods: The European Society for Paediatric Nephrology Dialysis Working Group (ESPN Dialysis WG) have developed recommendations for the choice of access type, pre-operative evaluation, monitoring, and prevention and management of complications of different access types in children with ESKD. Results: For adults with ESKD on haemodialysis, the principle of "Fistula First" has been key to changing the attitude to vascular access for haemodialysis. However, data from multiple observational studies and the International Paediatric Haemodialysis Network registry suggest that CVLs are associated with a significantly higher rate of infections and access dysfunction, and need for access replacement. Despite this, AVFs are used in only ∼25% of children on haemodialysis. It is important to provide the right access for the right patient at the right time in their life-course of renal replacement therapy, with an emphasis on venous preservation at all times. While AVFs may not be suitable in the very young or those with an anticipated short dialysis course before transplantation, many paediatric studies have shown that AVFs are superior to CVLs. Conclusions: Here we present clinical practice recommendations for AVFs and CVLs in children with ESKD. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system has been used to develop and GRADE the recommendations. In the absence of high quality evidence, the opinion of experts from the ESPN Dialysis WG is provided, but is clearly GRADE-ed as such and must be carefully considered by the treating physician, and adapted to local expertise and individual patient needs as appropriate.